Effect of distal embolization on myocardial perfusion reserve after percutaneous coronary intervention: a quantitative magnetic resonance perfusion study. - Selvanayagam, J; Cheng, A; Jerosch-Herold, M; Rahimi, K; Porto, I; van Gaal, W; Channon, K; Neubauer, S; Banning, A (2007)
BACKGROUND: Studies have shown that a subset of patients demonstrate persistent impairment in microcirculatory function after percutaneous coronary intervention (PCI). Distal embolization of plaque contents has been postulated as the main mechanism for this. We sought to investigate this further by evaluating PCI-induced changes in myocardial perfusion reserve index (MPRI) over time in segments with "distal-type" procedure-related myonecrosis using high-resolution quantitative cardiovascular magnetic resonance imaging. METHODS AND RESULTS: Forty patients undergoing PCI were studied with pre-PCI and 24-hour post-PCI delayed-enhancement magnetic resonance imaging and first-pass perfusion magnetic resonance imaging at rest and stress. Twenty patients underwent a third magnetic resonance imaging scan at 6 months. For perfusion imaging, 3 short-axis images were acquired during every heartbeat with a T1-weighted turboFLASH sequence. MPRI was calculated as the ratio of hyperemic to resting myocardial blood flow and subdivided according to the presence and location of new delayed hyperenhancement. Twenty-one patients demonstrated new distal hyperenhancement after PCI. Mean MPRI in revascularized myocardial segments not demonstrating new HE was significantly increased after the procedure (2.06 [95% CI, 1.99 to 2.13] before PCI and 2.52 [95% CI, 2.42 to 2.62] after PCI; P<0.001). In contrast, MPRI in segments with distal hyperenhancement was reduced after PCI (2.16 [95% CI, 1.95 to 2.37] before PCI; 2.00 [95% CI, 1.82 to 2.19] after PCI; mixed-model z=-4.82; P<0.001). Changes in mean MPRI 24 hours after PCI in segments upstream to new injury were not significantly different compared with perfusion changes in remote myocardium (z=-0.68; P=0.50). At 6 months after the procedure, mean MPRI in segments with new injury improved significantly compared with MPRI measured in these segments at 24 hours after PCI. CONCLUSIONS: MPRI is reduced in myocardial segments that demonstrate new distal irreversible injury at 24 hours after PCI. These reductions are confined to the segments with injury and do not affect the entire supply territory of the culprit vessel.